Chromatin variation associated with liver metabolism is mediated by transposable elements. Issue 1 (December 2016) - Du, Juan; Leung, Amy; Trac, Candi; Lee, Michael; Parks, Brian; Lusis, Aldons; Natarajan, Rama; Schones, Dustin
Abstract Background Functional regulatory regions in eukaryotic genomes are characterized by the disruption of nucleosomes leading to accessible chromatin. The modulation of chromatin accessibility is one of the key mediators of transcriptional regulation, and variation in chromatin accessibility across individuals has been linked to complex traits and disease susceptibility. While mechanisms responsible for chromatin variation across individuals have been investigated, the overwhelming majority of chromatin variation remains unexplained. Furthermore, the processes through which the variation of chromatin accessibility contributes to phenotypic diversity remain poorly understood. Results We profiled chromatin accessibility in liver from seven strains of mice with phenotypic diversity in response to a high-fat/high-sucrose (HF/HS) diet and identified reproducible chromatin variation across the individuals. We found that sites of variable chromatin accessibility were more likely to coincide with particular classes of transposable elements (TEs) than sites with common chromatin signatures. Evolutionarily younger long interspersed nuclear elements (LINEs) are particularly likely to harbor variable chromatin sites. These younger LINEs are enriched for binding sites of immune-associated transcription factors, whereas older LINEs are enriched for liver-specific transcription factors. Genomic region enrichment analysis indicates that variable chromatin sites at TEs may function to regulate liver metabolic pathways. CRISPR-Cas9 deletion of a number of variable chromatin sites at TEs altered expression of nearby metabolic genes. Finally, we show that polymorphism of TEs and differential DNA methylation at TEs can both influence chromatin variation. Conclusions Our results demonstrate that specific classes of TEs show variable chromatin accessibility across strains of mice that display phenotypic diversity in response to a HF/HS diet. These results indicate that chromatin variation at TEs is an important contributor to phenotypic variation among populations.